Thermoresponsive Hydrogel‐Enabled Thermostatic Photothermal Therapy for Enhanced Healing of Bacteria‐Infected Wounds - Hao Fu; Ke Xue; Yongxin Zhang; Minghui Xiao; Kaiyu Wu; Linqi Shi; Chunlei Zhu (Advanced Science, 2023)
Abstract Photothermal therapy (PTT) has emerged as an attractive technique for the treatment of bacterial infections. However, the uncontrolled heat generation in conventional PTT inevitably causes thermal damages to healthy tissues and/or organs. It is thus essential to develop a smart and universal strategy to regulate the photothermal equilibrium temperature to a preset safe threshold. Herein, a thermoresponsive hydrogel‐enabled thermostatic PTT system for enhanced healing of bacteria‐infected wounds is reported. In this system, the near‐infrared (NIR)‐triggered heat generation by photothermal nanomaterials is spontaneously transferred to a thermoresponsive hydrogel with a lower critical solution temperature (LCST), leading to its rapid phase transition by forming considerable light‐scattering centers to block NIR penetration. Such a dynamic and reversible process automatically regulates the photothermal equilibrium temperature to the phase‐transition point of the LCST‐type hydrogel. In contrast to temperature‐uncontrolled conventional PTT with severe thermal damages, the thermoresponsive hydrogel‐enabled thermostatic PTT provides effective protection on healthy tissues and/or organs, which remarkably accelerates wound healing by efficient bacterial eradication. This study establishes a smart, simple and universal PTT platform, holding great promise in the safe and efficient treatment of bacterial skin infections.